Helicene Chemistry From Synthesis to Applications - Chen, Chuan-Feng.; Shen, Yun.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2017)
This book systematically reviews recent advances in the synthetic methods and applications of helicenes. The first part of this book introduces the nomenclature and structural features of helicenes. The second part reviews several classic and useful methods as well as recently-developed approaches for the preparation and functionalization of helicenes, including photocyclization and Diels-Alder reactions, which are two important breakthroughs in the syntheses of helicenes. In the last part, the applications of helicenes in asymmetric syntheses, molecular machines, molecular recognition, self-assembly and other fields are discussed. This book provides a useful reference source for researchers and graduate students working not only in the area of helicene chemistry, but also in other research areas including materials science, supramolecular chemistry, coordination chemistry, and physical organic chemistry. Chuan-Feng Chen is a Professor at the Institute of Chemistry,Chinese Academy of Sciences, China.
Part I What Are Helicenes? -- Introduction to Helicene Chemistry -- Structures and Properties of Helicenes -- Part II How to Prepare Helicenes? -- Oxidative Photocyclization -- Diels-Alder and Friedel-Crafts-Type Reactions -- Metal-Mediated Reactions -- Other Synthetic Methods -- Asymmetric Synthesis -- Reactivity and Transformations -- Part III What Are the Applications of Helicenes? -- Helicenes in Catalysis -- Recognition, Sensors, and Responsive Switches -- Helicenes in Biochemistry -- Circularly Polarized Luminescence and Organic Electronics -- Helicene Assemblies.
Keywords: Chemistry, Organic; Catalysis; Optical materials; Physical chemistry; Organic Chemistry; Catalysis; Optical Materials; Physical Chemistry